A Survey on Nitrogen and Phosphorus Removal Efficiency from Dairy Industries Wastewater by Chemical Coagulation Combined with Fenton - Mohammad Javad Tahsini; Morteza Naseri (تحقیقات نظام سلامت, 2020)
Background: A high volume of wastewater is produced in dairy industries. These effluents contain high concentration of organic matters and nutrient elements (nitrogen and phosphorus). Discharging nitrogen and phosphorus to the environment leads to algal excessive growth, aquatics death, eutrophication and consequently, destruction of aquatic ecosystems. Methods: This study was an experimental-laboratory study that was carried out to evaluate the efficiency of nitrogen and phosphorus removal from dairy wastewater by combined process of chemical coagulation and Fenton. In the first stage, the effect of different doses of coagulant poly-aluminum chloride (PAC) on removal efficiency of Chemical oxygen demand (COD), Total Kjeldahl nitrogen (TKN), and total phosphorus (TP) was assessed and optimum dosage of coagulant was determined. Then, the supernatant was used in Fenton process and optimum values of reaction time, pH, H2O2 concentration and Fe2+ concentration was determined. Findings: According to the results, the optimal values were a PAC dosage equal to 100 mg/l, pH = 3, reaction time =  120 minutes, H2O2 concentration = 650 mg/l, and Fe2+ concentration = 150 mg/L. In optimal condition, maximum removal efficiency of COD, TKN, and TP was 91.70%, 76.58%, and 82.56% respectively. Conclusion: The results illustrated that the coupled process of chemical coagulation and Fenton oxidation might be an effective method to reduce nitrogen and phosphorus concentration in dairy wastewater.